Assertive speech acts in the YouTube Podcast Video “How Japanese people express our emotions with Ryoma” - Faishal, Najmi Muhammad; Saifudin, Akhmad (Universitas Dian Nuswantoro, 2024)
This study aims to describe and analyze the functions of assertive speech acts in a YouTube podcast video titled